Chironomidae fatty acid proportions - Scharnweber, Kristin (Uppsala University, 2019)
To test the predation effects of crucian carp (Carassius carassius), nutrient concentrations, and Chironomidae community composition on the fatty acid export from aquatic ecosystems, we conducted a 25-day experiment across 20 1,500-L mesocosms covering a total phosphorus (TP) gradient of 20–1,000 µg/L.
Our mesocosm facility was set-up in Lake Erken (59°51′N, 18°36′E) in Central Sweden, which is a mesoeutrophic lake with ambient concentrations of TP at 31 µg/L and total nitrogen (TN) at 0.7 mg/L (unpublished average of 25 years of monitoring). The mesocosms consisted of 20 white opaque, open-top cylinders with a flat bottom, made of high-density polyethylene that were 2 m deep and had a diameter between 92 and 101 cm. The floating mesocosms were attached to a dock close to the lakeshore.

Please see the manuscript "The emergence of fatty acids—Aquatic insects as vectors along a productivity gradient" by Scharnweber et al (2019) for further information about the study behind this dataset.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Chironomidae fatty acid proportions
Keywords: lakes; sjöar; fatty acid levels; fettvärden; fatty acids; fettsyror; Chironomidae; fjädermyggor; Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Natural Sciences; Naturvetenskap